Compensation for frivolous or vexatious prosecution - ONG, Benjamin Joshua (Institutional Knowledge at Singapore Management University, 2021)
According to section 359(3) of the Criminal Procedure Code, an acquitted accused person may receive compensation if the prosecution was “frivolous or vexatious”. In Parti Liyani v Public Prosecutor, Singapore’s High Court – for the first time – comprehensively discussed what section 359(3) means and how it is to be applied. This article aims to outline and comment on the High Court’s decision, and to highlight several issues which may be explored in future.